Technology Venture Blueprint NR Enterprise : The Multipurpose FANcy Broom / Nur Nabihah Mohammad Salleh - Salleh, Nur Nabihah Mohammad Salleh (2020)
NR Enterprise is a new company that wants to be world known as a unique, simple and easy household goods supplies. The products that is produced by NR Enterprise will be know as products to help and easy people works. We would supply happiness by producing useful products.